Research on food loss and waste in the Western Balkans: A systematic review - El Bilali, Hamid; Berjan, Sinisa; Ben Hassen, Tarek; Memon, Junaid Alam; Vaško, Željko; Allahyari, Mohammad S. (Frontiers in Nutrition, 2022)
Food losses and waste (FLW) is considered a critical issue in the ongoing debate on the sustainability of agri-food systems. However, the scholarly literature on FLW is still geographically-biased, with more attention devoted to developed countries, even in Europe. In this context, this article analyses the state of research on FLW in the Western Balkan region (viz. Bosnia and Herzegovina, Croatia, Montenegro, North Macedonia, and Serbia). A search performed in October 2021 on the Web of Science database returned 34 documents, and 21 eligible ones were included in the systematic review. The topical analysis of the literature addressed causes of FLW, stages of the food supply chain, extent and magnitude of FLW, FLW and food security, economic and environmental impacts of FLW, and food waste (FW) management strategies. A central finding was the scarcity of data on FW in the Western Balkans. Moreover, the literature focused on FW at the consumer level, while food loss at other stages of the food chain was generally overlooked. There is a lack of comprehensive analyses of the economic and environmental impacts of FLW as well as its implications in terms of food and nutrition security. The quantification of FLW is generally inaccurate and based on estimates and self-reported data. The literature focuses on FW reuse and recycling (e.g. energy, compost) while other management strategies (e.g. reduction/prevention, redistribution) are rarely addressed. However, the results indicated that consumers in the Western Balkans pay attention to the FW issue, especially during the COVID-19 pandemic, which is an encouraging sign that can be exploited in awareness-raising campaigns and education activities. Meanwhile, research on FLW in the Western Balkans is highly needed to fill the identified knowledge gap and provide evidence to policies dealing with the transition to sustainable food systems in the region.